The split between the creditor and the creditor’s court in maintenance obligations. Remarks on the jugment WV of the Court of Justice of the European Union - Marino, Silvia (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The present paper analyses the recent judgment WV of the Court of Justice of the European Union on maintenance obligations. The relevance of the case at stake stems from the fact that the claimant was a public body, who subrogated to the claims of a maintenance creditor, and acted against a debtor with habitual residence in another Member State. The Opinion of the Advocate General and thejudgment are a good opportunity to stress the innovative impact of Regulation No. 4/2009, the alternative character of the grounds of jurisdiction enshrined in Article 3 and the legal position of public bodies within the regulation on maintenance obligations.
Keywords: maintenance obligations; public bodies; jurisdiction; statutory subrogation